A new erythroneurine leafhopper genus from China (Hemiptera: Cicadellidae: Typhlocybinae) - Song, Yue-Hua; Li, Zi-Zhong (Zootaxa, 2013)
A new genus of tribe Erythroneurini from China, Laciniata gen. nov. is described and illustrated based on type species L. lijianga sp. nov.